The Effects of Vitamin D Supplementation on Metabolic and Oxidative Stress Markers in Patients With Type 2 Diabetes: A 6-Month Follow Up Randomized Controlled Study - Cojic, Milena; Kocic, Radivoj; Klisic, Aleksandra; Kocic, Gordana (Frontiers in Endocrinology, 2021)
Vitamin D deficiency could play an important role in the pathogenesis of type 2 diabetes mellitus (T2DM) as it may alter several crucial processes in the development of diabetes and its complications, such as pancreatic insulin secretion, peripheral insulin resistance, persistence of systemic „sterile“ inflammation and immune activation. Vitamin D may also have an antioxidant effect through the inhibition of free radicals generation. The reported study was designed with eligible consecutively recruited patients with T2DM on standard metformin therapy (n=130), randomized in 1:1 ratio, considered to have undergone Vitamin D supplementation according to the guidelines proposed by the Endocrine Society, or to have continued with metformin only. The potential benefit was monitored through the influence on glycemia level, glycated haemoglobin (HbA1c), insulin resistance index (calculated as homeostatic model assessment; HOMA-IR), Castelli Risk Index I and Tryglicerides/Thiobarbituric acid-reactive substances (TG/TBARS) Index in a 6-month follow up period. Our study indicates that oral daily doses of vitamin D improve HbA1c levels over the 3-month and 6-month period, followed by a significant decrease in advanced oxidation protein products levels over the 3-month period when higher vitamin D doses are given. The effect of vitamin D on HOMA-IR index, malondialdehyde levels and TG/TBARS index was not statistically significant. Further investigation should consider defining the doses of vitamin D in patients with T2DM which may attenuate the oxidative stress risk, the risk of metabolic syndrome and the risk of related cardiovascular events.